2019
DOI: 10.1111/jphp.13074
|View full text |Cite
|
Sign up to set email alerts
|

Abyssinone V, a prenylated flavonoid isolated from the stem bark of Erythrina melanacantha increases oxidative stress and decreases stress resistance in Caenorhabditis elegans

Abstract: Objectives Recent studies showed that distinct extracts of Erythrina species used in the traditional medicine of sub‐Saharan Africa are protective against stress conditions. However, the underlying molecular mechanisms as well as relevant compounds remain unclear. Methods We used the model organism Caenorhabditis elegans to investigate compounds isolated from the stem bark of Erythrina melanacantha (abyssinone V (1), abyssinon‐4′O‐methylether (2), sigmoidin B‐4′O‐methylether (3), glabranin (4), 8‐prenylnaringe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Moreover, we also found that acetophenone derivatives containing prenyl substituents show particularly higher cytotoxic activities compared to other compounds not bearing such structure elements. This finding was also reported for species of the genus Acronychia [25,39,[45][46][47] and we also observed such effects in our previous work with prenylated isoflavonoids and pterocarpanes from the genus Erythrina (Fabaceae) [48][49][50].…”
Section: Resultssupporting
confidence: 90%
“…Moreover, we also found that acetophenone derivatives containing prenyl substituents show particularly higher cytotoxic activities compared to other compounds not bearing such structure elements. This finding was also reported for species of the genus Acronychia [25,39,[45][46][47] and we also observed such effects in our previous work with prenylated isoflavonoids and pterocarpanes from the genus Erythrina (Fabaceae) [48][49][50].…”
Section: Resultssupporting
confidence: 90%
“…In contrast to the ABTS cation assay outcome described above, 8-PN (5–25 µM) was not able to reduce stable colored ABTS radicals in vitro in a more recent study. In the in vivo part of the same study, 8-PN at the tested 100 µM concentration slightly diminished intracellular accumulation of reactive oxygen species in Caenorhabditis elegans , but the inhibition did not reach statistical significance [ 189 ]. Overall, it thus appears that 8-PN has potential antioxidant activity, but this activity only emerges at relatively high concentrations.…”
Section: Other Beneficial and Adverse Effects Of 8-pnmentioning
confidence: 99%
“…A previous study has shown that nematode thermal stress is relevant to increasing oxidative stress ( Koch et al, 2019 ). In order to investigate the effect of nicotine on thermotolerance, all treated and untreated worms were moved to 37°C for three hours, and the number of live and dead OW13 worms was counted.…”
Section: Resultsmentioning
confidence: 99%
“…C . elegans’ oxidative stress increases with thermal stress ( Koch et al, 2019 ). The survival rate of nicotine-exposed worms was higher than untreated worms in a dose-dependent manner ( Figure 7B ).…”
Section: Discussionmentioning
confidence: 99%